2018
DOI: 10.1186/s12934-018-0988-6
|View full text |Cite
|
Sign up to set email alerts
|

Valuation of agro-industrial wastes as substrates for heterologous production of α-galactosidase

Abstract: BackgroundThe recycling of agro-industrial wastes is at present limited by the availability of efficient and low-cost enzyme cocktails. The use of these materials as culture media to produce the enzymes can contribute to the profitability of the recycling process and to the circular economy. The aim of this work is the construction of a recombinant yeast strain efficient to grow in mixed whey (residue of cheese making) and beet molasses (residue of sugar manufacture) as culture medium, and to produce heterolog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
12
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 37 publications
0
12
0
Order By: Relevance
“…In addition, the stability of the plasmid expressing ScAGal is not a problem since 98% of the cells growing in molasses retained the plasmid at the end of the cultures. In fact, we obtained a production of 30 U/mL of ScAGal which is 1.6-fold higher than the recently reported with a Kluyveromyces lactis engineered strain growing in a mixture of cheese whey and molasses (Álvarez-Cao et al, 2018) and higher than the 10.4 U/mL obtained for Aspergillus fumigatus alpha-galactosidase expressed in A. sojae in an optimized synthetic medium in the presence of 10.5% (w/v) molasses (Gurkok et al, 2011). The alpha-galactosidase yield reached is among the highest of those obtained in submerged fermentation for the alpha-galactosidase enzyme of different origins on various carbon sources (Anisha, 2017).…”
Section: Discussionmentioning
confidence: 49%
See 1 more Smart Citation
“…In addition, the stability of the plasmid expressing ScAGal is not a problem since 98% of the cells growing in molasses retained the plasmid at the end of the cultures. In fact, we obtained a production of 30 U/mL of ScAGal which is 1.6-fold higher than the recently reported with a Kluyveromyces lactis engineered strain growing in a mixture of cheese whey and molasses (Álvarez-Cao et al, 2018) and higher than the 10.4 U/mL obtained for Aspergillus fumigatus alpha-galactosidase expressed in A. sojae in an optimized synthetic medium in the presence of 10.5% (w/v) molasses (Gurkok et al, 2011). The alpha-galactosidase yield reached is among the highest of those obtained in submerged fermentation for the alpha-galactosidase enzyme of different origins on various carbon sources (Anisha, 2017).…”
Section: Discussionmentioning
confidence: 49%
“…The cost of the enzyme actually limits the profitability of most of the above cited applications. The use of cheap sub-products, such as molasses and whey, as substrates for production of ScAGal, was previously reported and might favor the economy of the processes (Álvarez-Cao et al, 2018). The aim of this work is to develop a system for the valuation of beet molasses, based on their use as substrate for ScAGal and bioethanol production by S. cerevisiae in two-steps.…”
Section: Introductionmentioning
confidence: 99%
“…Generally, metal ions have been shown to be relevant in enzyme activity. It has been reported that some metal ions such as Ag + , Cr +3 , Cu +2 , Fe +3 , Hg +2 , Mn +2 , Pb +2 , and Zn +2 inhibited α-galactosidase activity (Gote et al 2006;Álvarez-Cao et al 2018).…”
Section: Discussionmentioning
confidence: 99%
“…The huge amounts of low-cost byproducts are generated by agro-industrial activities and these are susceptible to be transformed in culture media for the production of highvalue-added bio-products such as ethanol and other biofuels, enzymes, and heterologous proteins (Álvarez-Cao et al 2018;Álvarez-Cao et al 2019).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation